Strategi Pemasaran Dan Harga Mobil Honda Dalam Mencapai Kesuksesan Di Indonesia - Ghani Abdur Rahman; Advent Chandra; Mohamad Zein Saleh (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research employs a qualitative method to analyze Honda's marketing and pricing strategies in Indonesia, focusing on product innovation, branding, digital marketing, customer experience, and adaptation to government policies and market trends. The findings indicate that Honda successfully captures consumer attention through advanced technology, strong branding, creative campaigns, and collaborations with influencers. Competitive pricing strategies and high-quality after-sales services also contribute to Honda's success in the Indonesian automotive market. The study provides recommendations for Honda to continue innovating in environmentally friendly technology, strengthening digital marketing, enhancing customer experience, and expanding collaborations with strategic partners. Additionally, the development of hybrid and electric vehicles and collaborations with technology companies are deemed essential to maintain competitive advantage in the future. By implementing these recommendations, it is expected that Honda can maintain and improve its position in the Indonesian automotive market.